Agglomeration and embeddedness of Belgian biotech firms: The role of venture capital - Katja Bringmann; Ann Verhetsel; Thomas Vanoutrive; Jo Reynaerts (European Regional Science Association (ERSA), 2013)
The existing literature on cluster embeddedness largely neglects the impact of finance on the development of firm?s network linkages. This is striking in so far that particularly venture capital is often referred to as ?smart money? providing firms not only with funds but also with network contacts. Thus, in this paper, we intend to quantitatively assess the impact of venture capitalists on start-ups? embeddedness. Embeddedness generally occurs along three dimensions namely the societal, the network and the territorial one. Societal embeddedness refers to the cultural environment economic actions take place in. Network embeddedness representing the structure and nature of relations an organization is maintaining and territorial embeddedness implying the degree of spatial anchoring of a firm in a specific geographical area. It is assumed that for firms and regions there are several advantages arising from deep network and, respectively, territorial embeddedness: Among others, they include local knowledge spillovers which promote innovative thinking and, subsequently, strengthen firms? global competitiveness and thereby fueling regional economic growth. In addition, particularly territorial embeddedness is reckoned as shielding to some extent against firm relocation that is widely regarded as hampering regional development. Due to the riskiness of their business, insufficient hard assets, and an unforeseeable rate of return, innovative startups are generally unable to get capitalized by more conventional sources of money i.e. bank lending and therefore often return to venture capital. Besides providing incumbent innovative firms with funds, venture capitalists, reverting to their vast sectoral knowledge and personal contacts, are frequently facilitating the entry of startups into existing personal and industry networks. Generally, it is anticipated that those network contacts are densest in the immediate neighbourhood of the investor. Summing up, given its ?social? character, it is hypothesized that venture capital is an important driver of start-ups? embeddedness that is nevertheless spatially constraint. In order to answer to what extent venture capital impacts portfolio firms? territorial and network embeddedness and whether the geographical location of the venture capitalist has an effect on start-ups? local anchoring, we conduct an empirical analysis using data on venture capital flows. By reviewing cluster embeddedness from a financial geographic perspective, this analysis complements the literature that hitherto has largely neglected the role of venture capital in this respect.
Keywords: R12; G24; 330; Venture capital; Industrial Cluster; Embeddedness; Social Networks